Detection of Cervical Cytological Abnormalities by Pap smears Method among Women Attending the Screening Clinic of Nsambya Hospital - Boaz, Mwesigwa; Okwi, Andrew Livex; Emmanuel, Othieno (Journal of Pathology Research Reviews and Reports, 2019)
Cervical cancer is an important public health problem. In Uganda, it ranks the most frequent cause of cancer among women aged between 15 to 44 years of age. Early detection and eradication of cervical cancer and its precursor lesions is the mainstay for control of this disease. The Pap smear method is the most cost-effective means of screening cervical pre-malignant, malignant processes and non-neoplastic lesions. Aim: To describe the cervical cytological abnormalities as detected byPap smear method and to determine the prevalence of such abnormalities Methodology: This was a prospective study, in which a total of 175 women were recruited from May to June, 2016. Cervical samples were collected from these women and stained according to the papanicolaou staining protocol. Results were reported using the 2014 Bethesda reporting system. Results: Out of 175 cases, 163 (93.1%) were reported as negative for intraepithelial lesion or malignancy [NILM]. Cervical intraepithelial lesions were reported in 12 (6.9%) cases which included atypical squamous cells of undetermined significance [ASCUS] in 4(2.3%) cases, atypical squamous cells cannot exclude high grade squamous intraepithelial lesions [ASCH] in 1(0.6%) case, low-grade squamous intraepithelial lesion [LSIL] in 5 (2.9%) cases, high-grade squamous intraepithelial lesion [HSIL] in 1(0.6%) case and atypical glandular cells [AGC] in 1(0.6%) case. Conclusion: Cervical cytology by Pap smear method should be used to screen women routinely because it is an effective method in detecting pre-malignant and malignant lesions of the cervix.
Keywords: Cervical Cancer; Cervical Intraepithelial Neoplasia; Human Papilloma Virus; Papanicolaou Smear